Data Warehouse Design Academic Affairs Case Study: Campus II STMIK STIKOM Bali Jimbaran - Surya, Putu Bagus Hendrayana; Rahardian, Rifky Lana; Oka Saputra, Komang (International Journal of Engineering and Emerging Technology, 2017)
At the management level, the information becomes a factor in the decision making process. It takes a form of support for different data processing of transactional data processing form that allows the leadership of obtaining accurate information and in a short time, so that will give birth to independence in obtaining information. Information on the student data needed by a coordinator academic campus to see the conditions in which academic information only from a centralized database in BAAK. To overcome these problems need to design a data warehouse for the system dashboard for campus coordinator can monitor academic conditions.